FUNCTION MONITORING AND RECOVERY METHODS IN THE REHABILITATION OF TENNIS PLAYERS - Yin,Jiabao (2022)
ABSTRACT Introduction Sports injury is a common injury among professional tennis players compared to other sports. Updated rehabilitation methods can accelerate players’ recovery and ensure a return to sporting activity. However, contemporary rehabilitation monitoring practices want updated reporting. Objective Monitoring tennis players’ function and recovery methods during rehabilitation training after injury. Methods The tennis player underwent arthroscopic capsulotomy of the left ankle joint, free body removal, and synovectomy. The athlete’s body composition, blood routine, biochemistry, nutritional indices, and physiological indicators were monitored. Data were collected before, during, and at the end of the four months (6-10 months) of rehabilitation after the operation. Results 1 month after the operation, weight and lean mass decreased significantly; body fat percentage increased; static heart rate increased significantly (P<0.05). Three months after surgery, the athlete’s lean mass increased significantly to 43.7 kg; body fat percentage decreased to 24.5% (P<0.05); hemoglobin, serum iron, total protein, and albumin improved; in rehabilitation during October, blood routine and biochemical blood indices were regular; Resting, maintained-load and recovery heart rate decreased significantly (P<0.05). Conclusion Tennis players should begin function monitoring, rehabilitation training, and nutritional recovery as soon as possible after ankle joint surgery. Evidence Level II; Therapeutic Studies - Investigating the result.